2015
DOI: 10.1590/0104-530x1568-14
|View full text |Cite
|
Sign up to set email alerts
|

Dimensões da inovatividade organizacional e seu impacto no desempenho inovador: proposição e avaliação de um modelo

Abstract: O estudo propõe um modelo teórico que representa as condições organizacionais habilitadoras da inovação (definido, no estudo, como inovatividade) e avalia o impacto no desempenho inovador. Emprega-se a correlação canônica como forma de avaliar a capacidade do modelo em explicar a variação do desempenho inovador em 120 organizações de médio e grande porte localizadas, em sua maioria, no sul do Brasil. Os resultados indicam que as condições identificadas são consistentes em expressar as melhorias inovadoras nas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
11
0
5
Order By: Relevance
“…Additionally, innovativeness has been tested by other researchers in a theoretical model representing the organizational conditions that enable innovation and influence innovation performance (Quandt et al, 2015). These authors identified that innovative organizations, with strongly developed organizational culture, leadership and learning processes, achieve superior performance in development and implementation of innovations.…”
Section: Organizational Innovativenessmentioning
confidence: 99%
“…Additionally, innovativeness has been tested by other researchers in a theoretical model representing the organizational conditions that enable innovation and influence innovation performance (Quandt et al, 2015). These authors identified that innovative organizations, with strongly developed organizational culture, leadership and learning processes, achieve superior performance in development and implementation of innovations.…”
Section: Organizational Innovativenessmentioning
confidence: 99%
“…Numerous studies have focused on the measures of process to evaluate the degree of innovation in firms (Beyhan et al, 2009). In any event, Quandt, Bezerra, and Ferraresi (2015) postulate that these measures are insufficient in gauging the elements that lead to innovation. Accordingly, there is a need to investigate the conditions that enable the organization to be innovative.…”
Section: Dimensions Of Organizational Innovationmentioning
confidence: 99%
“…Their model comprises an integrated and dynamic set of capacities, behaviors, processes and activities which promote the innovation. The model derives from the extant research, and uses these dimensions in a recurrent manner, as shown in Table 2 (Quandt, Bezerra and Ferraresi, 2015). There is evidence in the relationship of processes with better innovation outcomes than product-based vision.…”
Section: Dimensions Of Organizational Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Este modelo, parte do pressuposto de que é necessário não somente distinguir as capacidades dinâmicas das básicas, mas também analisar o processo de evolução das capacidades, focando na sua afetividade (Salazar & Peláez, 2011). Cabe destacar que este Página | 115 modelo conceitual limita-se a uma avaliação das dimensões internas, que estão sob o domínio da organização (Quandt, Bezerra & Ferraresi, 2015).…”
Section: A Inovação E a Inovatividade Organizacionalunclassified